Influência das variáveis antropométricas e cinemáticas no desempenho do salto com queda lateral em goleiros de futebol de campo - Elano Silva de Magalhães Berto (2022)
The objective of the present study was to verify the contribution of the variables, height, wingspan, performance in the vertical jump (SV), reaction time (TR) and speed of displacement of a marker point corresponding to the Center of Mass (CM), in the performance of the jump defense with lateral takedown on goalkeepers. The sample consisted of twenty-two male goalkeepers, with at least three years of practice in the specific position, under-20 category, from five elite clubs in Brazilian football. At the first moment, height, wingspan, length of lower limbs and performance in vertical jumps were measured. Next, the goalkeepers performed an action simulating a defense with a lateral drop jump. The athletes were instructed to position themselves in the center of the goal (goal) and, in response to a visual stimulus, start the defense movement. Kinematic analysis was used to obtain movement time, reaction time and displacement speed of the marked point approaching the CM. The level of bivariate relationship between the total time of execution of the task and the independent variables height, wingspan, vertical jump performance, reaction time and displacement speed was determined by Pearson's linear correlation coefficient (r). As the bivariate correlation was significant, the next step was to perform multiple linear regression in order to quantify the level of influence of the independent variables on the dependent variable. The goodness of fit of the model was evaluated by the adjusted R2 value, which is equal to the percentage of variation in the dependent variable that is explained by the variance of the independent variables. The results showed that the multiple linear regression model composed of the independent variables reaction time, SV height, in addition to the anthropometric variables, height, wingspan and length of the lower limbs (IMC) and the jump technique given by the vertical component of the velocity in take-off phase, were able to predict the movement time until contact with the ball (s), with an explained variance of 83.5%.